2009
DOI: 10.1007/s00421-009-1201-8
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise-induced extracellular 72 kDa heat shock protein (Hsp72) stimulates neutrophil phagocytic and fungicidal capacities via TLR-2

Abstract: This study evaluated the role of toll like receptor 2 (TLR-2) in the interaction of 72 kDa extracellular heat shock protein (Hsp72, a stress-inducible protein) with neutrophils and the participation on TLR-2 in the stimulation of neutrophil phagocytic and fungicidal capacities by post-exercise physiological concentrations of Hsp72. Human peripheral blood neutrophils were incubated with fluorescein isothiocyanate-conjugated Hsp72, and were analyzed by immunofluorescence microscopy and flow cytometry. Both metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
3
30
1
Order By: Relevance
“…5). Potential additional sterile inflammatory signals that are known to interact with TLRs and to increase in the circulation after strenuous exercise include endogenous nucleic acids (4,17), such as circulating cell-free Microarray log2 fold change qPCR log2 fold change DNA (2, 3), free fatty acids (4, 13), and HSPs (14), in particular the stress-inducible isoform of the HSP70 family, HSP72 (1,12). Considering previous studies showing increases in plasma/serum HSP70/72 concentrations immediately after intense, prolonged exercise (10,34,56) and a decrease thereafter (34, 56), we might have missed detecting a significant plasma HSP70 response at 3 h post-EXTRI, similar as with cortisol (23, 56).…”
Section: Discussionmentioning
confidence: 99%
“…5). Potential additional sterile inflammatory signals that are known to interact with TLRs and to increase in the circulation after strenuous exercise include endogenous nucleic acids (4,17), such as circulating cell-free Microarray log2 fold change qPCR log2 fold change DNA (2, 3), free fatty acids (4, 13), and HSPs (14), in particular the stress-inducible isoform of the HSP70 family, HSP72 (1,12). Considering previous studies showing increases in plasma/serum HSP70/72 concentrations immediately after intense, prolonged exercise (10,34,56) and a decrease thereafter (34, 56), we might have missed detecting a significant plasma HSP70 response at 3 h post-EXTRI, similar as with cortisol (23, 56).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria of untrained muscles released sustained higher levels of reactive oxygen species, whereas progressive adaptation to exercise lowered the production of free radicals through abrogation of NFkB and activator protein-1 (AP-1) pathway (Brookes et al 2008). Concurrently with the modulation of the antioxidant factors there is induction of other cytoprotective factors such as chaperones or heat shock proteins (HSPs), as well as the regulation of the nuclear kappa beta (NFkB) proliferating factor, increasing synthesis of the antiinflammatory cytokine IL-10, and decreasing production of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α), IL-1, IL-6, and further reduction of inflammatory lineages of monocytes (CD14 + /CD16 + ) (Timmerman et al 2008;Czarkowska-Paczek et al 2009;Giraldo et al 2010;Rahman et al 2010;Ropelle et al 2010) in response to physical exertion. In this sense, it was observed that skeletal muscle activation of nitric oxide synthesis is dependent on heat shock protein-90 (HSP90) expression (Harris et al 2008).…”
Section: Regular Physical Exercise: Adaptation To Oxidative Stress Anmentioning
confidence: 99%
“…The neutrophils’ phagocytic and fungicidal capacities against C. albicans were evaluated ex vivo using a quantitative technique previously validated for isolated neutrophils [13,14]. Briefly, 0.5 ml of C. albicans suspension (10 6 cells/ml) and 50 µl of serum were added to 0.5 ml of the neutrophil suspension (10 6 cells/ml), followed by incubation in a thermostatic bath at 37°C for 60 min with shaking.…”
Section: Methodsmentioning
confidence: 99%